1989
DOI: 10.1007/bf00005725
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of structural and functional adaptation in epilithon exposed to zinc

Abstract: Artificial streams were used to study the effect of chronic zinc dosing (0.00,0.05 or 1.00 mg Zn 1-') on epilithic communities during summer and early fall, 1984 and 1985. Following zinc addition, epilithon was periodically measured for '4C-glucose and 14C-glutamate respiration, ash-free dry weight (AFDW), protein, carbohydrate, chlorophyll a (Chl a), pheophytin a (pheo a), and colony forming units (CFU) on zinc amended and unamended media. Transient peaks in glucose respiration rates mg-' protein and AFDW occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
6
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
3
6
0
Order By: Relevance
“…Moreover, under HL condition, the specific growth rate of this strain was decreased by high zinc concentration. Our results are in accordance with previous studies indicating that long-term high zinc concentration exposure can decrease the growth rate of diatoms and cyanobacteria (Colwell, Hornor, and Cherry 1989;Loez, Topalian, and Salibian 1995).…”
Section: Discussionsupporting
confidence: 96%
“…Moreover, under HL condition, the specific growth rate of this strain was decreased by high zinc concentration. Our results are in accordance with previous studies indicating that long-term high zinc concentration exposure can decrease the growth rate of diatoms and cyanobacteria (Colwell, Hornor, and Cherry 1989;Loez, Topalian, and Salibian 1995).…”
Section: Discussionsupporting
confidence: 96%
“…The similarity in bacterial abundance to the different metal concentrations, but with significant changes over the study period, is further indicative of tolerance by the exposed bacterial populations within the assemblages to the metal treatments. These observation corroborates earlier similar studies that have also reported high metal tolerance over time by indigenous bacterial assemblages in aquatic environments . For instance, Kim et al reported that the addition of copper slightly stimulated bacterial growth in the microlayers as compared to subsurface water in their study.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the lack of concentration-dependent toxicity of both metal treatments on the indigenous bacterial populations as observed in this study is not uncommon and the reasons could be attributed to and/or explained by various factors including, the bacterial transformation of metals such as mercuric chloride and methyl mercury to elemental mercury [32], complexation of the metals with organic matter [33], and through bacterial incorporation and accumulation [28,34]. In particular, Colwell et al [28] suggested that the tolerance of and adaptation to Zn exposure observed was as a direct results of the incorporation of Zn within the structural milieu of the epilithic biofilm assemblages in their study. Freshwater environments are known to comprise of relatively high concentrations of various inorganic nutrients, such as chlorides and nitrates primarily due to several anthropogenic disturbances [15,16].…”
Section: Discussionmentioning
confidence: 57%
“…This has been reported in pure culture biofilm studies in which Pseudomonas aeruginosa adopted a metal-resistant phenotype when exposed to metal contamination (69). Colwell et al (12) found that the numbers of Zn-tolerant bacteria increased with time in periphyton exposed to 1 mg of Zn liter Ϫ1 . Similarly, Vaccaro et al (72) found an increase in Cu tolerance of heterotrophs during a marine mesocosm experiment.…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with both a potential loss of redundancy and recruitment of resistant taxa. It is also important to note here that the interaction between different biological components of the community (bacteria, microalgae, and protozoa) and sorption of contaminants by the biofilm will complicate the community responses and their interpretation (12,24,55).…”
Section: Discussionmentioning
confidence: 99%